2023
DOI: 10.4103/ija.ija_672_23
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of analgesic effects of pericapsular nerve group block and fascia iliaca compartment block during hip arthroplasty: A systematic review and meta-analysis of randomised controlled trials

Jay Prakash,
Bram Rochwerg,
Khushboo Saran
et al.

Abstract: Background and Aims: Postoperative pain for patients having hip arthroplasty ranges from moderate to severe. Many regional anaesthesia procedures treat postoperative pain to improve functional ability and quality of life. Evidence comparing the analgesic effects of the pericapsular nerve group (PENG) block and fascia iliaca compartment block (FICB) remains unclear. The analgesic efficacies of PENG and FICB in hip arthroplasty were compared to determine which technique is associated with superior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Another analysis [36] showed no difference in pain scores at 6, 12, and 24 h between PENG and FICB, but the mean opioid consumption in morphine equivalents was significantly lower with PENG compared to FICB. Prakash et al [37] observed no difference between the PENG block and FICB at 24 h for pain at rest and movement, while the PENG block showed improved analgesia within 30 min at rest and during movement, along with reduced postoperative opioid consumption within 24 h. Randomized controlled trials (RCTs) showed that the PENG block did not exhibit clinically significant differences in postoperative pain scores or cumulative opioid consumption compared to suprainguinal FICB [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Another analysis [36] showed no difference in pain scores at 6, 12, and 24 h between PENG and FICB, but the mean opioid consumption in morphine equivalents was significantly lower with PENG compared to FICB. Prakash et al [37] observed no difference between the PENG block and FICB at 24 h for pain at rest and movement, while the PENG block showed improved analgesia within 30 min at rest and during movement, along with reduced postoperative opioid consumption within 24 h. Randomized controlled trials (RCTs) showed that the PENG block did not exhibit clinically significant differences in postoperative pain scores or cumulative opioid consumption compared to suprainguinal FICB [38,39].…”
Section: Discussionmentioning
confidence: 99%